2020
DOI: 10.5152/ejbh.2019.5004
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Clinicopathological Features, Metastasis Sites and Survival Outcomes of Invasive Lobular, Invasive Ductal and Mixed Invasive Ductal and Lobular Breast Carcinoma

Abstract: Invasive breast cancer is a histologically heterogeneous disease; among numerous histological types, invasive ductal carcinoma (IDC) is the most common, present in 70%-75% of the cases (1, 2), followed by invasive lobular carcinoma (ILC), present in 5%-15% of the cases (1-3). Mixed invasive ductal and lobular carcinoma (IDLC), which has characteristics of both invasive ductal and lobular carcinoma, is present in approximately 5% of the cases (2). Lately, the prevalence of the lobular breast tumors has been on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 30 publications
3
19
1
Order By: Relevance
“…Many previous studies investigated the prognosis of IDC, ILC, and IDLC with inconsistent results [3-9, 11, 12, 15, 16]. Some found a similar prognosis between ILC and IDC [3,4,8,16], while others found that ILC showed better OS compared with IDC [6]. In the present study, there were no differences in BCSS between IDC and ILC in the multivariate model.…”
Section: Discussioncontrasting
confidence: 64%
See 2 more Smart Citations
“…Many previous studies investigated the prognosis of IDC, ILC, and IDLC with inconsistent results [3-9, 11, 12, 15, 16]. Some found a similar prognosis between ILC and IDC [3,4,8,16], while others found that ILC showed better OS compared with IDC [6]. In the present study, there were no differences in BCSS between IDC and ILC in the multivariate model.…”
Section: Discussioncontrasting
confidence: 64%
“…A recent study found that patients with IDLC had better disease-free survival and OS compared with ILC among postmenopausal women only with 204 cases of ILC and 258 cases of IDLC, while no survival differences were observed between IDLC and ILC in the total population [12]. Like many previous studies [9,11,16,20], the present study did not find any differences in BCSS and OS between IDLC and ILC before and after matching by the Kaplan-Meier curves. However, the subgroup analysis showed significant improvement in survival of ILC over IDLC in HR(+)HER2(+) and HR(−)HER2(−) subgroups.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Invasive lobular carcinoma (ILC) usually meets the definition of luminal A cancer, showing high ER and PR expression, with Ki-67 lower than 20%. Nevertheless, ILC long term prognosis does not differ from that of IBC of no special type 35 , 36 depending mostly on TNM staging at presentation 35 , 37 .…”
Section: Introductionmentioning
confidence: 90%
“…Although ER+ ILC and IDC tumors are treated clinically as a single disease (9), recent studies have established ER+ ILC as a distinct disease with unique sites of metastasis, frequent presentation of multifocal disease, delayed relapses, and decreased long-term survival compared to ER+ IDC tumors (10)(11)(12)(13)(14). Large-scale studies from The Cancer Genome Atlas (TCGA) and the Molecular Taxonomy of Breast Cancer International Consortium (METABRIC) have reported genomic and transcriptomic analyses on resected IDC and ILC tumors (15,16).…”
Section: Introductionmentioning
confidence: 99%